Nilai Kepemimpinan Edukatif Ki Hajar Dewantara Dalam Perspektif Tafsir Ibn Kathir atas Surat Ali Imran:159 - Ratna Sundari Puspitosari; Enjang Burhanudin Yusuf (Journal of Community Development, 2025)
Ki Hajar Dewantara, as the Father of Indonesian Education, inherited the philosophy of educational leadership known as "Ing Ngarso Sung Tuladha, Ing Madya Mangun Karsa, Tut Wuri Handayani". In the Qur'an, Surah Ali Imran verse 159, interpreted by Ibn Kathir, a leader must have a gentle attitude, consult, forgive and not be hard-hearted. Educators in this context are teachers, leaders in the learning process in the classroom who will lead their students to achieve the National Education Goals. These two values are interrelated and need to be actualized in education in Indonesia. Using a qualitative research method with a content analysis approach to analyze and interpret texts from two different sources. Previous research only focused on one theme, there has been no research that integrates the 3 pillars of Ki Hajar Dewantara's Education with Ibn Kathir's interpretation of QS. Ali Imran verse 159. The purpose of this study is to synthesize the educational leadership values of Ki Hajar Dewantara in relation to QS. Ali Imran verse 159 using the interpretation of Ibn Kathir. The theoretical and practical benefits of this study are to provide new knowledge for teachers on how to correlate Ki Hajar Dewantara's philosophy with the characteristics contained in QS. Ali Imran verse 159 when becoming a learning leader in the classroom. The synthesis of the two sources is Ing Ngarso Sung Tuladha with a gentle and non-violent attitude, Ing Madya Mangun Karsa with deliberation or discussion, and Tut Wuri Handayani with a forgiving attitude. The Indonesian education system needs to strengthen aspects of character and ethical values in addressing social problems and violence. This is important to support the formation of an empathetic and responsible young generation